2015
DOI: 10.1038/leu.2015.334
|View full text |Cite
|
Sign up to set email alerts
|

FOXM1 is a therapeutic target for high-risk multiple myeloma

Abstract: The transcription factor forkhead box M1 (FOXM1) is a validated oncoprotein in solid cancers, but its role in malignant plasma cell tumors such as multiple myeloma (MM) is unknown. We analyzed publicly available MM datasets and found that overexpression of FOXM1 prognosticates inferior outcome in a subset (~15%) of newly diagnosed cases, particularly patients with high-risk disease based on global gene expression changes. Follow-up studies using human myeloma cell lines (HMCLs) as the principal experimental mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 63 publications
8
50
0
Order By: Relevance
“…6B). This activity is consistent with transgenic mice models showing that FOXM1 expression promotes early steps in tumorigenesis, promoting Clara cell and hepatocyte hyperplasia for example(69,70) and acting in conjunction with many other carcinogens (71) as well as cancer cell lines(72,73). Replication stress has been shown to be a source for genomic instability in pre-neoplasic lesions, while in normal cells replication stress leads to cell death or , as it reproduces many of the outcomes for RIGI reported in other model systems.…”
supporting
confidence: 84%
“…6B). This activity is consistent with transgenic mice models showing that FOXM1 expression promotes early steps in tumorigenesis, promoting Clara cell and hepatocyte hyperplasia for example(69,70) and acting in conjunction with many other carcinogens (71) as well as cancer cell lines(72,73). Replication stress has been shown to be a source for genomic instability in pre-neoplasic lesions, while in normal cells replication stress leads to cell death or , as it reproduces many of the outcomes for RIGI reported in other model systems.…”
supporting
confidence: 84%
“…We reported that NEK2 is highly expressed in several cancer types, such as cholangiocarcinoma (22), breast (7, [23][24][25][26][27][28][29][30][31], colorectal (27,(32)(33)(34)(35), and pancreatic (36,37) cancer. Consistently, several researchers reported that high expression of NEK2 is identified in various cancer types, including testicular seminoma (27,38,39), cervical tumor (27), primary liver cancer (40), hepatocellular carcinoma (8, 41), prostate cancer (27,42), lung cancer (27,(43)(44)(45), ovarian cancer (46), renal cell cancer (47,48), myeloma (49), peripheral nerve sheath tumors (50), follicular lymphoma (51,52) and diffuse large B-cell lymphoma (52).…”
Section: Nek2 Expression In Cancermentioning
confidence: 60%
“…More recently, FOXM1 was shown to play a critical role in the maintenance of Glioblastoma stem cell 24 . FOXM1 upregulation was also observed in blood cancers including ALL 25 and myeloma 26 . Inhibition of FOXM1 reduced proliferation in AML leukemia cell lines 27 .…”
mentioning
confidence: 91%